The Implication of Hotel Tax Collection towards the Increase of the Regional Original Revenue at Tangerang Regency Based on the Principle of Good Governance - Pipih Ludia Karsa; Fatkhul Muin (Universitas Muhammadiyah Ponorogo, 2019)
The law, as an important part of the society, regulates all legal aspects, which in it includes the aspect of taxation law. It must be oriented to justice in the society, therefore, the values must represent the interests of the society. Hotels are facilities which provide services in the form of lodging/resting area, including the other services which are related, with some charge. This also includes motels, guesthouses, tourism huts, tourism guesthouses, tourism boarding houses, inns, etc., also boarding houses with more than ten rooms. Tangerang Regency is one of the areas which has a high potential in the hospitality sector to increase the Regional Original Revenue (Pendapatan Asli Daerah/PAD). Based on Tangerang Regency’s Regional Regulations No. 10 year 2010 regarding Regional Tax, the regional government of Tangerang Regency withdraws the tax of that region, in which in it includes hotel tax. The hotel tax provisions in Tangerang regency are based on that regulation, where tax are withdrawn from the hotels for the services they provide.